INTEGRASI NILAI KEUTAMAAN UMAT ISLAM DALAM KURIKULUM PENDIDIKAN ISLAM SUATU ANALISIS KONSEPTUAL HADITS QUDSI - Miqdad Abdussalam, Muhammad; Sartika, Dewy; Akmansyah, Muhammad; Syahril, Sultan (As-Sulthan Journal of Education, 2025)
This research aims to analyze the integration of the values of excellence for the Muslim ummah in the Islamic education curriculum through a conceptual study of the first Qudsi hadith. The approach employed is literature-based conceptual analysis, examining various sources such as journals, articles, and classical texts. The research findings indicate that the Qudsi hadith plays a significant role in strengthening the spiritual, moral, and social dimensions of Islamic education. The values contained within it, such as mercy, justice, patience, and sincerity, not only enrich theological understanding but can also be integrated as core competencies in the Islamic education curriculum. This integration fosters the balanced character development of students across cognitive, affective, and spiritual aspects. Furthermore, the Qudsi hadith serves as a moral foundation for instilling universal values like compassion, social responsibility, and civilized justice. Thus, reinforcing the values of excellence for the ummah through education becomes a crucial strategy in building a generation of Muslims who are noble in character, moderate, and relevant to global challenges.